2015
DOI: 10.7759/cureus.257
|View full text |Cite
|
Sign up to set email alerts
|

How, When and Where to Discuss Do Not Resuscitate: A Prospective Study to Compare the Perceptions and Preferences of Patients, Caregivers, and Health Care Providers in a Multidisciplinary Lung Cancer Clinic

Abstract: Background: Do Not Resuscitate (DNR) is a significant but challenging part of end-of-life discussions when dealing with incurable lung cancer patients. We have explored the perceptions and preferences of patients, their caregivers (CGs), and health care providers (HCPs) and the current practice and opinions on DNR discussions in a multidisciplinary lung cancer clinic.Materials and Methods: This is a prospective descriptive study with a mixed quantitative and qualitative methodology to capture perceptions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…42 Practice was influenced by observation of other health professionals communicating DNACPR decisions with patients. 49 Most patients and caregivers had already thought about DNACPR in anticipation or preparation of having this discussion with the healthcare provider 32 ; with only 37.5% of them having DNACPR knowledge. DNACPR knowledge had a significant relationship with age and educational level 53 ; 57% of practitioners reported that providing information to the patient was important and 21% stated that this was likely to happen.…”
Section: Evidence Of Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Practice was influenced by observation of other health professionals communicating DNACPR decisions with patients. 49 Most patients and caregivers had already thought about DNACPR in anticipation or preparation of having this discussion with the healthcare provider 32 ; with only 37.5% of them having DNACPR knowledge. DNACPR knowledge had a significant relationship with age and educational level 53 ; 57% of practitioners reported that providing information to the patient was important and 21% stated that this was likely to happen.…”
Section: Evidence Of Discussionmentioning
confidence: 99%
“…Qualitative & mixed methods a question or uncertainty. 54 Patients' desires related to the seriousness of an imagined or future medical state 32 ; culture and religion are factors that can influence decision making, 17 55 56 76.2% of physicians rated the influence of religion on code status decisions and 82.9% of physicians rated the influence of culture. 29 Religion plays a role in making DNR decisions for 58.3% 31 and the importance of comfort during dying was a priority for 45.3%.…”
Section: Evidence Of Discussionmentioning
confidence: 99%
“…Higher educational levels among nurses meant having more confidence to deal with patients’ problems in clinical nursing practices [ 45 ]. Prior studies have shown that religious beliefs are a significant factor in forming caregivers’ and health care providers’ viewpoints about DNR decisions [ 46 , 47 ]. This significance is because religious beliefs play an essential role in the lives of many people since spiritual and ethical issues are usually aroused or strengthened as patients near end-of-life, as well as nurses on nursing practice behaviors toward the end-of-life care [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the physicians’ lack of time to carefully deliberate the appropriateness of writing a DNR order for the patient may relate to this finding. Since most DNR discussions are prompted by physicians, whether they bring the DNR discussion up can significantly influence patients’/surrogates’ DNR decisions [35, 36]. Physicians who were tasked with caring for a higher volume of patients per day might have had less time to carefully deliberate whether or not cardiopulmonary resuscitation is useful or harmful.…”
Section: Discussionmentioning
confidence: 99%